Traditional Chinese Medicine Integrated with Chemotherapy for Stage II-IIIA Patients with Non-Small-Cell Lung Cancer after Radical Surgery: A Retrospective Clinical Analysis with Small Sample Size. (25th July 2018) - Zhao, Xueyu; Dai, Xiaojun; Wang, Shanshan; Yang, Ting; Yan, Yan; Zhu, Guang; Feng, Jun; Pan, Bo; Sunagawa, Masataka; Zhang, Xiaochun; Qian, Yayun; Liu, Yanqing
Abstract : Objective . This study was designed to evaluate the clinical efficacy of combined traditional Chinese medicine (TCM) and conventional chemotherapy versus conventional chemotherapy in patients with stage II-IIIA non-small-cell lung cancer (NSCLC) after radical surgery. Methods . A retrospective cohort study was conducted in patients with stage II-IIIA NSCLC from Subei People's Hospital and Yangzhou Traditional Chinese Medicine Hospital in Yangzhou City of Jiangsu Province from 2012 to 2016. Patients were divided into two groups: the TCM user group (patients receiving treatment with integrated TCM and conventional chemotherapy) and the non-TCM user group (patients receiving conventional chemotherapy only). The two groups were compared for their median disease-free survival (DFS) and median overall survival (OS). Results . A total of 67 patients with stage II-IIIA NSCLC were enrolled between January 2012 and December 2016. The median DFS for the non-TCM user group was 601 days (95% confidence interval [CI], 375.7-826.3). The median DFS for TCM user group could not be calculated. However, log-rank analysis showed that the median survival time in the TCM user group was significantly longer than that of the non-TCM user group (P < 0.05). In addition, several significant risk factors were detected for predicting disease prognosis in patients with NSCLC, such as age, ECOG, lymphatic metastasis, and body mass index (BMI). For patients harboring these independent risk factors, the DFS of TCM user group was much longer than that of non-TCM user group (P < 0.05). Conclusion . Adjuvant therapy with TCM may reduce the rate of tumor recurrence and metastasis and prolong DFS of patients with stage II-IIIA NSCLC.